Source of Cadmium (Cd) In Soils and Its Transfer to Rice and Vegetables: Karotia Union, Tangail - Shamim Al Mamun; Reyad Hossain Arif; Md Ariful Islam; Md Sirajul Islam; Zakia Parveen; Muliadi Muliadi (Hasanuddin University, 2020)
Cadmium is a trace element which is not essential for human being. High cadmium concentration in some rice samples in Bangladesh was reported than that of other countries. This study was carried out to find out the Cd concentration fertilizers, soils, rice and vegetables and along with other chemical properties of Karotia union, Tangail sadar upazila, Tangail. A total of 29 samples were collected among the 14 soils from 7 stations at 0-15 cm and 16-30 cm depth respectively, 5 vegetables, 5 rice and also 4 different countries TSP fertilizers from local market. The Cd concentration values of all soil samples were found between 0.97 to 1.73 mg/kg (0-15 cm) and 0.53 to 0.83 mg/kg (16-30 cm), respectively and the vegetable sample values were found between 0.053 mg/kg to 0.123 mg/kg (d.w.).The rice sample values were found between 0.05 mg/kg to 0.096 mg/kg (d.w.). The fertilizer sample values were found between 20.67 to 92.33 mg/kg. The soil pH values obtained 7.06 to 7.70 (0-15 cm) and 7.48 to 7.88 (16-30 cm) which indicated that the study area soils were neutral to moderately alkaline. The EC values of all soil samples were between 47.67 to 82.67dSm-1 (0-15cm) and 33.33 to 58.33dSm-1 (16-30 cm). The organic matter content of all soils ranged from 0.789 to 0.905% and 0.351 to 0.869% at (0-15 cm and 16-30 cm), respectively. The available sodium (Na) values of soils were found between 1.84 to 1.92 ppm (0-15 cm) and 1.83 to 1.90 ppm (16-30 cm), respectively. The available potassium values ranged from 1.81 to 1.96 ppm (0-15 cm) and 1.84 to 1.97 ppm (16-30cm), respectively. The available calcium values of all soil samples were 1.92 to 1.97 ppm (0-15 cm) and 1.91 to 1.96 ppm (16-30 cm), respectively.